Correction to: Consensus on best practice standards for Fracture Liaison Service in the Asia-Pacific region (Archives of Osteoporosis, (2018), 13, 1, (59), 10.1007/s11657-018-0463-3) - Chan D.-C.D. (Springer London, 2019)
10.1007/s11657-018-0485-x